Bad Dames - Palazón Blasco, Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Once upon a time, before History, in some stories, she was Our Lady. Then He arrived and threw her out of the world, out of reality, out of His Book. The old goddess took refuge in the borders of the world (in the desert, in the mountains), in the margins of reality (in dreams), in the outskirts of the Book. From these other places, from these hiding places, she jumps on careless men, enjoys them, and beheads them, or bleeds them dry, or castrates them. Lilith, from Mesopotamia, Lamia, from Libya, the Empusas, from Greece, our serranas, the troglodyte, black Virgins, are all aspects of this brave lady, are the bad dames that men try to lock up inside the bottle of His Word. None of them has a father, or a Father. Fatherless, they are the only ones who don’t play the daughter and can, because of that, desire. No wonder they are scary.